PENGARUH PENGGUNAAN MEDIA VIDIO YOUTUBE TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA MATERI KALIMAT EFEKTIF STUDI PADA SISWA KELAS IV SD MUHAMMADIYAH 10 TALLO - lisma, Lisma; Rahman Rahim, Abdul; Akhir, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of YouTube video media on the learning outcomes of fourth-grade students in the Indonesian language, particularly in the effective sentences section, at Muhammadiyah 10 Elementary School, Tallo. This study used a quantitative approach with a Pre-Experimental Design in the form of a One Group Pretest-Posttest Design. The sample consisted of 23 students, selected using a saturated sampling technique. The results showed that the average pretest score was 60, which is in the low category, while the average posttest score increased to 85.86, which is in the high category. The percentage of student learning completion also increased, from 13.04% in the pretest to 91.30% in the posttest. The results of the hypothesis test showed that the calculated t-value of 11.98 was greater than the t-table of 1.717 at a significance level of 0.05 (11.98 > 1.717), thus H₀ was rejected and H₁ was accepted.